(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2023)
The FloWatt project aims to demonstrate the efficiency of the HydroQuest’s 2.5 MW-rated turbine for commercial farm deployment. The project is dedicated to develop an innovative design of a turbine for high energetic sites and to deploy seven vertical axis tidal turbines on the Raz Blanchard site, France. This technology has already been successfully developed in a previous project at a smaller scale on the Paimpol-Bréhat test site. Along the past three years, an important amount of work has been achieved to widely characterise the behaviour of the 1/20 scale 2-VATT similar to the 1MW-rated demonstrator. The turbine was tested in many different operating conditions in the Ifremer’s wave and current flume tank to reproduce full-scale conditions and turbine response (wide range of operating points and incident velocities, facing aligned and misaligned currents, with and without vertical velocity shear, with and without bathymetry generated turbulence, with and without surface waves following and against the current). Based on that experience, we gain confidence in the design process by comparing those experimental results to numerical and in-situ ones. After a quick presentation of the industrial development for the deployment of a pilot farm with the manufacture, installation and operation of 7 turbines on the Raz-Blanchard site, we will focus on the scientific development aiming to prepare large-scale deployments of the next generation of turbine. One important step is to compare the flow-induced loading between the 2 kinds of turbine (ducted and unducted) and to analyse environmental loads during survival conditions. To investigate those points, the behaviour of a 1/20 scale 2-VATT similar to the 2.5 MW-rated demonstrator is experimentally studied in a wide range of operating conditions: with and without vertical velocity shear, and with and without surface waves following and against the current. In the paper, we will compare at 1/20 scale the behaviour of the two kinds of turbine: 1 MW-rated and 2.5 MW-rated turbines. The experiments have been done in the same basin, under the same experimental conditions. The databases are being processed before launching a fine physical analysis.